Pengaruh Capital Adequacy Ratio, Non Performing Loan dan Return On Asset Terhadap Penyaluran Kredit - Dewanti Safitri; Asep Muslihat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine whether there is an influence of capital adequacy ratio, non-performing loans, return on assets, lending. The effect of capital adequacy ratio financing on lending, the effect of non-performing loans on lending and the effect of return on assets on lending, and capital adequacy ratios, non-performing loans and return on assets on lending. 44 samples were taken from 2016 to 2019 with data on monthly capital adequacy ratios, non-performing loans, return on assets, and lending. The statistical methods taken in this research are multiple analysis, classic assumption test, descriptive statistical analysis, determination analysis and hypothesis testing using SPSS 25 analytical tools.In this research, we know the effect of capital adequacy ratio, non-performing loans, and return on assets in partial or joint lending. This method is a descriptive verification method with a quantitative approach to the source of annual financial statements at commercial banks. Purposive sampling technique. The data obtained were analyzed by testing the validity of the data, multiple linear regresis analysis and hypothesis testing using the f test and t test.The results of this study show that the partial capital adequacy ratio has a negative effect on lending, non-performing loans on lending have a positive effect and the return on assets on lending has a positive effect. Whereas jointly the credit distribution is very influential. Keywords: Capital Adequacy Ratio, Nonperforming Loans, Return On Assets, Lending